PERAN FASILITAS PEMBELAJARAN DAN KREATIVITAS DALAM MENINGKATKAN HASIL BELAJAR SISWA BISNIS DIGITAL PADA MATERI DESAIN LOGO DI SMKS PGRI 13 SURABAYA - Aulia Masyitha; Septyan Budy Cahya (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2026)
This research aims to describe the role of learning facilities and creativity in improving Digital Business student learning outcomes on logo design material at SMKS PGRI 13 Surabaya. This research was motivated by limited learning facilities and low student creativity which had an impact on less than optimal learning outcomes, especially in the Digital Branding subject. This research uses a qualitative approach with descriptive methods. Data collection techniques are carried out through interviews, observation and documentation. The research results show that learning facilities have not been utilized optimally due to limited access to computer laboratories, limited equipment, and students' use of personal devices with varying specifications. This condition has an impact on students' limited opportunities to practice and explore logo design. In addition, students' creativity shows variations, where some students still experience difficulties in developing ideas and tend to rely on templates, while students with higher creativity are able to develop ideas, modify designs, and are active in the revision process. Therefore, optimizing learning facilities and developing student creativity are important factors in improving learning outcomes in logo design learning.